A Quality Improvement Initiative Is Associated With Reduced Time to Administer Biologics and Small Molecules and Emergency Room Visits in Inflammatory Bowel Disease. Issue 3 (7th March 2022) - Battat, Robert; Galati, Jonathan S.; Lukin, Dana; Chabouni, Fatiha; Sockolow, Robbyn; Carter, Jeff; Fajardo, Kristina; Yang, Stevie; Reich, Jenna; Jacobs, Vinita; Abramowitz, Meira; Kumar, Anand; et al.
Abstract : Background: Delays in biologic or small molecule medication administration are associated with increased adverse events, hospitalization, and surgery in inflammatory bowel disease (IBD). We evaluated the impact of a quality improvement (QI) intervention on the time to administration of biologics or small molecules (TABS) in IBD. Methods: Data were retrospectively extracted for IBD patients prescribed biologics or small molecules from a convenience sample of providers participating in an accredited QI educational intervention (baseline cohort). Subsequent to the intervention, data were prospectively collected from patients prescribed these medications (postintervention cohort). Dates related to steps between a treatment decision to medication administration were collected. The primary outcome compared TABS in baseline and postintervention cohorts. Results: Eighteen physicians provided survey and patient data for 200 patients in each cohort (n=400). The median time to medication administration (TABS) decreased from baseline to postintervention cohorts (30 vs. 26 d, P =0.04). Emergency room visits before medication administration also decreased (25.5% vs. 12.5%, P =0.001). Similar numerical TABS reductions were observed in subgroups limited to physicians providing patients to both cohorts and for individual medications prescribed. Primary contributors to delays included filling prescriptions subsequent to insurance approval and dispensation subsequent to this. Conclusions: A QI intervention successfully reduced medication administration times (TABS) by accelerating provider-dependent steps. This intervention was associated with reduced emergency room visits. We propose TABS as a quality metric to assess the effective delivery of therapies in IBD. Further evaluation of QI interventions, patient education on prescription drug insurance, and quality metrics are warranted.